Design of novel microstrip patch antenna for millimeter-wave B5G communications - Tiang, Jun Jiat; Alsekait, Deema Mohammed; Khan, Imran; Wang, Pi-Chung; Madsen, Dag Øivind (Frontiers in Materials, 2024)
Introduction: The simplicity of integration and co-type features of microstrip antennas make them intriguing for a broad variety of applications, particularly with the growing usage of mmWave bands in wireless communications and the constant rise in data transfer in communication situations. Method: This paper proposes a novel design of micrstrip patch antenna for mmWave B5G communication. The main idea is to realize four-mode antenna the operates in four different frequencies. The geometry is rectangular patch whose resonance frequency is adjusted by varying the walls and pins of the structure. Results: Simulation results show that the proposed antenna design has improved fractional bandwidth and performance as compared with existing antennas. Discussion: The observed curve indicates that, in agreement with the modeling findings, there are four resonance spots in the operational frequency region of 2.5–3.4 GHz: 2.68 GHz, 2.9 GHz, 3.05 GHz, and 3.3 GHz, which correspond to TM1/2,0, TM3/2,0, and TMRS, respectively, and TM1/2,2 four resonant modes, within the frequency range, the observed antenna gain peak is around 9 dBi, which is consistent with the measured results.